Purchase and Collection Motivations of Co-Branded Limited-Edition Collectibles: The case of the Jollibee Funko Pop - Santos, Joseph Emil; Vergara, Raymond Allan G. (Future Science / FSH-PH Publications, 2023)
This exploratory case study seeks to understand the purchase and collection motivations of an international co-branded limited-edition collectible. It also explores consumers’ perceptions of the brand collaboration between Philippine-based Jollibee and United States-based Funko. This study finds that consumers are motivated to purchase and collect products based on their willingness to identify with the brand, which stems from personal values, self-concept, and nostalgia. While most studies on co-branding use simulated alliances, this study provides a real example of an international branding collaboration, thereby providing a nuanced understanding of co-branding spillover effects and how a consumer’s willingness to identify with a brand motivates their purchase and collection decisions.